2014
DOI: 10.1002/path.4418
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 augments skeletal muscle regeneration after ischaemia–reperfusion injury

Abstract: Skeletal muscles harbour a resident population of stem cells, termed satellite cells (SCs). After trauma, SCs leave their quiescent state to enter the cell cycle and undergo multiple rounds of proliferation, a process regulated by MyoD. To initiate differentiation, fusion and maturation to new skeletal muscle fibres, SCs up-regulate myogenin. However, the regulation of these myogenic factors is not fully understood. In this study we demonstrate that Nrf2, a major regulator of oxidative stress defence, plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…CBR1 inhibition is associated with an increase of ROS production, and with impaired differentiation and skeletal muscle regeneration in vivo (190). Consistently, skeletal muscle regeneration is strongly delayed in Nrf2-deficient animals, where alteration in the time course of myogenesis is observed and has been attributed to an alteration of MuSC proliferation/differentiation balance (4,304).…”
Section: E Myogenic Differentiationmentioning
confidence: 75%
See 1 more Smart Citation
“…CBR1 inhibition is associated with an increase of ROS production, and with impaired differentiation and skeletal muscle regeneration in vivo (190). Consistently, skeletal muscle regeneration is strongly delayed in Nrf2-deficient animals, where alteration in the time course of myogenesis is observed and has been attributed to an alteration of MuSC proliferation/differentiation balance (4,304).…”
Section: E Myogenic Differentiationmentioning
confidence: 75%
“…Higher levels of GSH are found in type I muscle fibers, which have an oxidative/aerobic metabolism, as compared with type II fibers, which rely mainly on a glycolytic/anaerobic metabolism (185). 4. Family of thioredoxins.…”
Section: A Endogenousmentioning
confidence: 99%
“…FPKM values for myosin heavy chain 4 (Mhy4), which is the most abundant myosin type in rodent gastrocnemius associated with the fastest most glycolytic fibers (IIb), was also decreased. 2 Looking at other sarcomeric components, BCATm KOs expressed higher amounts of genes encoding slower fiber (I) types of troponin C and myosin binding protein C (Tnnc1, Mybpc1), whereas the faster twitch fiber types (Tnnc2, Mybpc2) were decreased ( Table 4). The Mb gene encoding the O 2 -carrying protein, myoglobin, associated with more oxidative fiber types, was 2 During this part of our bioinformatics evaluation, it was noticed that Myh4, normally a major gene and protein component in muscle, had 0 FPKM values for several animals.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2/ARE signalling is activated by acute exercise stress in the myocardium (14). Several previous studies have suggested that the role of Nrf2 goes beyond antioxidant mechanisms (15,16). Al-Sawaf et al (16) reported that Nrf2 regulated myogenic regulatory factor (Mrf) expression and that Nrf2-knockout retarded skeletal muscle regeneration after injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have suggested that the role of Nrf2 goes beyond antioxidant mechanisms (15,16). Al-Sawaf et al (16) reported that Nrf2 regulated myogenic regulatory factor (Mrf) expression and that Nrf2-knockout retarded skeletal muscle regeneration after injury. Heat shock proteins (HSPs) have also been reported to have a cytoprotective role in skeletal muscles (17).…”
Section: Introductionmentioning
confidence: 99%